The Implementation of Business Intelligence to Analyze Sales Trends in the Indofishing Online Store Using Power BI - Sri Anardani; Muh Nur Luthfi Azis; Moch Yusuf Asyhari (Brilliance: Research of Artificial Intelligence, 2023)
The growth of online sales businesses by utilizing E-Commerce is increasing rapidly. One way that can be used as a tool to face competition is to apply Business Intelligence as a basis for making the right business strategy decisions. Indofishing Shop is an online shop selling various fishing gear and equipment. So far, online sales transaction data processing uses Microsoft Excel, which has created problems with the need for more information to analyze product trends. This research applies Business Intelligence to detect data extracted and collected in a data warehouse. The data will be analyzed statistically and visualized using Microsoft Power BI. Data warehouse design uses Kimball's Nine-Step method. The results of this research are in the form of a visualization dashboard that is used to analyze sales trends for the most sold fishing equipment products from the Indofishing Shop. Diagram visualization helps Indofishing understand the trend conditions of the most in-demand products and the cities of origin of the buyers who buy the most products.